Norberto Bobbio: judicial norms and political rules - Eduardo Carlos Bianca Bittar (Prisma Jurídico, 2004)
This article intends to show that Norberto Bobbio thought is dynamic – that some times focus discussion of legal system… and other times the social and political values –, ever detaching the difference of the author theories and his observations.